Reflection Practice in Microteaching: Evidence from Prospective Science Teachers - Marlina, Reni; Suwono, Hadi; Yuenyong, Chokchai; Ibrohim, Ibrohim; Hamdani, Hamdani (Universitas Islam Negeri Raden Intan Lampung, 2023)
Professional education courses such as microteaching are currently placing greater emphasis on reflective activities, particularly in the context of the new paradigm curriculum in Indonesia. The aim of this study is to investigate the ability of prospective teachers to reflect on their microteaching experiences, the common aspects discussed during reflection activities, and the peer feedback provided regarding lesson plan design and implementation within a microteaching setting. The study employs a sequential explanatory mixed-methods design and spans 13 weeks with 122 teacher candidates who participated in a flipped learning setting. Flipped learning was chosen as the instructional model to potentially enhance the level of collaboration in learning activities. Results revealed that flipped learning can indeed foster a collaborative environment among prospective teachers. Further, the most commonly identified aspect appearing in the reflections was the modeling of teaching techniques, outweighing other aspects such as classroom management, learning tools, lesson duration, pedagogical strategies, and student learning processes. These findings offer valuable insights for prospective teachers, particularly regarding feedback and reinforcement practices in microteaching. Moreover, this research suggests that flipped learning could be a promising approach to cultivating these practices. Future studies are recommended to further investigate the potential of different instructional models in enhancing reflection and collaboration among teacher candidates.